Sistem Informasi Pariwisata Babel Berbasis Android - Ifano, Duhan; Irwan, Irwan (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
The android-based Bangka Belitung tourism information system is used to make it easier for tourists in Bangka Belitung and those from outside, to obtain information about tourism, cultural customs, souvenirs, and culinary delights available in Bangka Belitung. This android application is made using the waterfall method which consists of several stages, namely requirements analysis, system design, programming, testing, and implementation. This application will display detailed information on tours, cultural customs, souvenirs, and culinary delights in Bangka Belitung. Based on the results of black box testing and user acceptance testing (UAT) by conducting questionnaires to 10 users, the percentage results are 89%. Therefore, the authors developed a Bangka Belitung tourism information system using Android Studio and PhpMyAdmin as MySQL database management. With this Android application, it can make it easier for local tourists and tourists from outside Bangka Belitung to find information about tourism in Bangka Belitung.